Take a Peek! Into Lagu Melayu Asli (Universitas Negeri Semarang, 2022)
Every music have their own unique identities. All these inimitable feature is something that need to be expose and publish, or else it it perish. With that in mind, this paper explore or as titled suggested, “Take a Peek!” into Lagu Melayu Asli or Malay Asli song. In doing so, an extensive documents analysis was conducted as our methodology processes. After relevant documents in Lagu Melayu Asli gathered, we using qualitative content analysis technique to investigate most distinctive characters in Lagu Melayu Asli. To strengthen our arguments, personal interview were conducted. In discussion, a discourse of summarizing facts that found within literature presented in two dimensional ways, instrumentation related in Lagu Melayu Asli and musicological aspect of Lagu Melayu Asli.